2022
DOI: 10.1186/s12916-022-02295-3
|View full text |Cite
|
Sign up to set email alerts
|

Imagery ability assessments: a cross-disciplinary systematic review and quality evaluation of psychometric properties

Abstract: Background Over the last two centuries, researchers developed several assessments to evaluate the multidimensional construct of imagery. However, no comprehensive systematic review (SR) exists for imagery ability evaluation methods and an in-depth quality evaluation of their psychometric properties. Methods We performed a comprehensive systematic search in six databases in the disciplines of sport, psychology, medicine, education: SPORTDiscus, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 170 publications
(363 reference statements)
0
16
0
Order By: Relevance
“…Indeed, education and level of physical activity were statistically different between the groups and are known to modify motor imagery abilities 39 . Although the MIQ-RS is a commonly used questionnaire 45 , and seems to be a reliable and valid tool [37][38][39] , it is not well balanced between upper and lower extremity questions, with 10 of the 14 questions focused on upper extremity MI abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, education and level of physical activity were statistically different between the groups and are known to modify motor imagery abilities 39 . Although the MIQ-RS is a commonly used questionnaire 45 , and seems to be a reliable and valid tool [37][38][39] , it is not well balanced between upper and lower extremity questions, with 10 of the 14 questions focused on upper extremity MI abilities.…”
Section: Discussionmentioning
confidence: 99%
“…All these results suggest that the Spanish version of the MIQ-3 is a reliable measure of MI capacity for use in institutionalized elderly people. The study by Suica et al [ 29 ] showed that the questionnaires for assessing MI with the best psychometric properties were the Movement Imagery Questionnaire (MIQ) [ 45 ] as well as its versions Movement Imagery Questionnaire—Revised (MIQ-R) [ 46 ], MIQ-3, and the Vividness of Movement Imagery Questionnaire (VMIQ-2) [ 47 ]. The same study showed that most studies assessing MI had been conducted in a young population [ 29 ], thus highlighting the need to validate MI assessment tools in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Suica et al [ 29 ] showed that the questionnaires for assessing MI with the best psychometric properties were the Movement Imagery Questionnaire (MIQ) [ 45 ] as well as its versions Movement Imagery Questionnaire—Revised (MIQ-R) [ 46 ], MIQ-3, and the Vividness of Movement Imagery Questionnaire (VMIQ-2) [ 47 ]. The same study showed that most studies assessing MI had been conducted in a young population [ 29 ], thus highlighting the need to validate MI assessment tools in the elderly. On the other hand, of all these questionnaires, only the MIQ-3 and the VMIQ-2 assess MI ability and MI vividness, respectively, in the three subscales of internal visual, external visual, and kinesthetic imagery [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been claimed that kinesthetic imagery, olfactory imagery, audio imagery, and visual imagery modalities can be employed in imagery exercise [24]- [28]. Kinesthetic imagery refers to the sensation of movement while acting.…”
Section: Introductionmentioning
confidence: 99%